2022
DOI: 10.1186/s12887-022-03511-y
|View full text |Cite
|
Sign up to set email alerts
|

A new approach to skin extravasation injury management during the neonatal period

Abstract: Background To identify a standard protocol for managing extravasation injuries in neonates. Methods We recruited all the neonates with extravasation wounds from the neonatal intensive care unit of Shariati hospital, Tehran, Iran, between October 2018 and October 2020. Sixteen patients with grade 3–4 extravasation were evaluated in this retrospective study. All grade 3 and 4 extravasation wounds were injected with hyaluronidase at 5 points of the wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…4 Drug extravasation can cause swelling and pain at the site in mild cases, and tissue necrosis, muscle contracture, and functional sequelae may result in severe cases, which may cause medical or nursing disputes. 5 The occurrence of adverse reactions of subcutaneous exudation of intravenous human immunoglobulin is related to many factors, such as the age of the child, dosage, infusion site, and infusion speed. 1,6 In this case, the child was a small infant with congenital heart disease and severe pneumonia with recurrent infections, poor peripheral circulation in the extremities, and suboptimal vascular conditions.…”
Section: Discussionmentioning
confidence: 99%
“…4 Drug extravasation can cause swelling and pain at the site in mild cases, and tissue necrosis, muscle contracture, and functional sequelae may result in severe cases, which may cause medical or nursing disputes. 5 The occurrence of adverse reactions of subcutaneous exudation of intravenous human immunoglobulin is related to many factors, such as the age of the child, dosage, infusion site, and infusion speed. 1,6 In this case, the child was a small infant with congenital heart disease and severe pneumonia with recurrent infections, poor peripheral circulation in the extremities, and suboptimal vascular conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Although the efficacy of hyaluronidase in preventing injury in IV injuries has not been demonstrated in randomized controlled trials in humans, it remains a recommended antidote (28). Several studies have shown the positive effect of hyaluronidase (150 U/mL solution) in managing extravasation in infants (14,19,20,24,25,29). However, this drug is not recommended in infants less than 28 weeks because the skin of these infants is considered too premature (3).…”
Section: Hyaluronidasementioning
confidence: 99%
“…In their study in Iran, Sagheb et al used hot compresses in 16 infants in the first 24 hours after extravasation injury and the subcutaneous administration of hyaluronidase. After 24 hours, they applied other managements (washing with normal saline, using fibrinolysin ointment, and dressing with phenytoin) (20). In a study in Turkey, Altan et al used limb elevation and cold compress for a 23-day-old girl who was injured in the forearm after contrast injection (17).…”
Section: Hot and Cold Compressesmentioning
confidence: 99%
“…Preface Fat Emulsion is an intravenously administered nutrition drug, and it is widely used in clinical practice [1,2]. However, skin damage is common due to its high concentration and high permeability, and extravasation is a common complication that affects drug absorption [3,4,5], destroys the integrity of skin and tissue, and causes obvious pain [6,7]. A detachable hydropathic compress is a new kind of wet compress method, which could effectively dilate blood vessels, improve blood circulation and reduce local pain.…”
Section: Introductionmentioning
confidence: 99%